Direct wafer bonding of Ga2O3–SiC at room temperature. Issue 5 (1st April 2019) - Xu, Yang; Mu, Fengwen; Wang, Yinghui; Chen, Dapeng; Ou, Xin; Suga, Tadatomo
Abstract: Integration of Ga2 O3 on SiC substrate with a high thermal conductivity is one of the promising solutions to reduce the self-heating of Ga2 O3 devices. Direct wafer bonding of Ga2 O3 –SiC at room temperature was achieved by surface activated bonding (SAB) using a Si-containing Ar ion beam. An average bonding energy of ~2.31 J/m 2 was achieved. Both the structure and the composition of the interface were investigated to understand the bonding mechanism. According to the interface analysis, a ~2.2 nm amorphous SiC layer and a ~1.8 nm amorphous β-Ga2 O3 layer originating from the ion beam bombardment for surface activation were found at the interface. A slight diffusion at the interface might already happen at room temperature, which should contribute to the strong bonding. To confirm the diffusion at a low temperature and investigate the possible interfacial variation during device operation, an annealing process was carried out at 473 K. The same analysis was applied on the annealed bonding interface. The interfacial layer shrank by ~0.5 nm after annealing. The further diffusion of Ga and Si at the interface caused by the annealing was confirmed. Besides, the position of the Ar count peak inside the amorphous Ga2 O3 layer shifted by ~0.5 nm toward SiC.